The Perils of Being a Male Primary/Junior Teacher: Vulnerability and accusations of inappropriate contact with students - Parr, Michael; Gosse, Douglas (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
There is a perceived shortage of male teachers in education, particularly at the primary/junior (P/J) level where male teachers in Canada account for a dwindling minority. Included among the many factors inhibiting males from becoming P/J teachers are perceptions that males might be unduly vulnerable to false accusations of inappropriate conduct with pupils, frequently of a sexual nature. This paper highlights findings of research exploring the experiences of male P/J teachers in Ontario. Results of an online survey completed by 223 male P/J teachers are discussed; 28 of these teachers reported they had been suspected of having had inappropriate contact with pupils and wrote online comments outlining their experience. The findings are discussed in the context of what it means to be a male assuming a non-traditional role of working with young children in today’s milieu.